Scaling-up services for psychosis, depression and epilepsy in sub-Saharan Africa and South Asia: development and application of a mental health systems planning tool (OneHealth). (19th September 2016) - Chisholm, D.; Heslin, M.; Docrat, S.; Nanda, S.; Shidhaye, R.; Upadhaya, N.; Jordans, M.; Abdulmalik, J.; Olayiwola, S.; Gureje, O.; Kizza, D.; Mugisha, J.; et al.
Abstract : Background: Although financing represents a critical component of health system strengthening and also a defining concern of efforts to move towards universal health coverage, many countries lack the tools and capacity to plan effectively for service scale-up. As part of a multi-country collaborative study (the Emerald project), we set out to develop, test and apply a fully integrated health systems resource planning and health impact tool for mental, neurological and substance use (MNS) disorders. Methods: A new module of the existing UN strategic planning OneHealth Tool was developed, which identifies health system resources required to scale-up a range of specified interventions for MNS disorders and also projects expected health gains at the population level. We conducted local capacity-building in its use, as well as stakeholder consultations, then tested and calibrated all model parameters, and applied the tool to three priority mental and neurological disorders (psychosis, depression and epilepsy) in six low- and middle-income countries. Results: Resource needs for scaling-up mental health services to reach desired coverage goals are substantial compared with the current allocation of resources in the six represented countries but are not large in absolute terms. In four of the Emerald study countries (Ethiopia, India, Nepal and Uganda), the cost of delivering key interventions for psychosis, depression and epilepsy at existing treatment coverage is estimated at US 0.06–0.33 per capita of total population per year (in Nigeria and South Africa it is US 1.36–1.92). By comparison, the projected cost per capita at target levels of coverage approaches US 5 per capita in Nigeria and South Africa, and ranges from US 0.14–1.27 in the other four countries. Implementation of such a package of care at target levels of coverage is expected to yield between 291 and 947 healthy life years per one million populations, which represents a substantial health gain for the currently neglected and underserved sub-populations suffering from psychosis, depression and epilepsy. Conclusions: This newly developed and validated module of OneHealth tool can be used, especially within the context of integrated health planning at the national level, to generate contextualised estimates of the resource needs, costs and health impacts of scaled-up mental health service delivery.